Occupational therapy and right to the city - Correia, Ricardo Lopes; Gonçalves, Monica Villaça (Cadernos Brasileiros de Terapia Ocupacional, 2021)
In this sense, the construct "collective occupations" (Ramugondo & Kronenberg, 2015) shows a strong convergence with the objective of this debate, in particular, on the formation and dynamics of social space. [...]our objective is to invite the category to a debate about a technicalepistemic perspective of occupational therapy in the field of urban issues, which values the understanding of everyday life in cities and promotes theories, processes, and technologies to outline practical actions and research in the area. [...]studies on human occupation have modified it over time (Reed et al., 2013), and, from more critical (Huff et al., 2020) and decolonizing (Simaan, 2020) historical perspectives, they have a centralized occupation in occupational therapy processes, as a historical, social and culturally constructed phenomenon. [...]in these studies, occupation is understood as a dimension of human doing, which contributes to the understanding and explanation of human experience, through the inseparable relationship between subjectcontext/environment, and offering support for therapeutic-occupational practices. Every subject can only be read within human life when signified by belonging to its community. [...]collective occupations are, in addition to occupational forms, the intention of getting involved collectively, comprising an act that implies strengths, roles, abilities, capacities, and meaning sharing in situations mutually identified for the cohesion and/or disjunction of the social fabric (Kantartzis & Molineux, 2017). According to Kantartzis & Molineux (2017), it makes it vulnerable and breaks with the networks of occupational opportunities, preventing subjects from being able to recognize the power of intentionality and collective exercise for local transformations.